HUBUNGAN ANTARA PENGENDALIAN DIRI DAN RELIGIUSITAS DENGAN PERILAKU SEKS BEBAS REMAJA - Afandi, Idris (STIT Al - Ibrohimy Bangkalan, 2018)
Relation between selfcontrol and Religiusity with Behavior of Adolescent Free Sex in SMPN 1 Klampis, District of Klampis Sub-Province of Bangkalan Purpose of this research is to know relation between and selfcontrol of religiusity with behavior of adolescent free seks. This research is studied in corelational quantitative. Research Subyek are the students of SMPN 1 Klampis class of VIII Pre-Eminent and Reguler with amount 100 adolescent early consisting of 54 men and 46 women with age about 12-15 years. Researcher developes three researches measuring instrument that is selfcontrol scale, Scale of religiusitas behavioral scale and adolescent free sex. Result of analysis of regretion express relation which is significant between selfcontroland religiusity with behavior of adolescent free sex. Result of from three the variable indicate that there are relations between selfcontrol and religiusity with free sex. With coefficient of determinasi ( R Square) equal to 0.207 or 20,7% both the variable influence free sexs and 79,3% influenced by variable which the others. To both of tables is obtained by effective contribution equal to 0. 125 or 12,5 % variable of religiusity influence free sex. While result of selfcontrol of free sex obtained negative relations between selfcontrol with free sex. With correlation coefficient equal to its 0,37,3 meaning of selfcontrol variable enough weaken to predict variable of free sex. At tables of measure association are obtained by effective contribution equal to 0.13,9 or 13,9% selfcontrol variable influence behavior of students free sex.